Noise Analysis in Pre-Amplifier Circuits Associated to Highly Sensitive Optically-Pumped Magnetometers for Geomagnetic Applications - Leisong Liu; Yuantian Lu; Xin Zhuang; Qunying Zhang; Guangyou Fang (Applied Sciences, 2020)
This paper analyzes the noise sources in photoelectric detection circuits with several low-noise operational amplifiers cores. The fabricated circuits are low-noise pre-amplifiers that are used for optically pumped magnetometers. In the proposed circuits, the noise levels of equivalent output voltage are calculated, and the results are in accordance with measurements. With a cooperation of several operational amplifiers, we select LT1028 from linear technologies as the core for our detection circuit, which has an output signal-to-noise ratio of more than 2 × 105 up to the frequency of 100 kHz. By analyzing the individual noise sources in the detection circuit, the dominant noise source is confirmed as the photocurrent shot noise below 200 kHz. Beyond this frequency, the voltage noise source in the operational amplifier dominates. Besides, the lamp power, the radio frequency (RF) power, the temperature variations, and their influences on the sensitivity are studied and optimized. Finally, an optically pumped magnetometer with cesium head is established, showing an intrinsic sensitivity of 85 fT/√Hz. This sensitivity is realized under a geomagnetic magnetic field strength of 53 μT.